Selection, Selection, Selection: the Impact of Return Migration - Jackline Wahba (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
The evidence on the impact of return migration on the sending country is rather sparse, though growing. The contribution of this paper is in addressing various selectivity problems whilst quantifying the impact of return migration on wages of returnees using non-experimental data. Using Egyptian household level survey data, I estimate the wages of return migrants controlling for several selectivity biases arising from emigration choice, return migration choice, labor force participation choice and occupational choice following return. The findings provide strong evidence that overseas temporary migration results in a wage premium upon return, even after controlling for the various potential selection biases. However the estimates underscore the significance of controlling for both emigration and return migration selections. Ignoring the double selectivity in migration would overestimate the impact of return migration on the wage premium of returnees, as migrants are positively selected relative to non-migrants, but returnees are negatively selected amongst migrants.
Keywords: F22; J24; O15; O53; 330; International return migration; Wages; Developing countries